Encyclopedia of Buddhism - Buswell, Robert E., Jr., 1953- (New York : Macmillan Reference, USA, 2004)
"Buddhism is one [of] the world's major religions with influences reaching far beyond its origins in East Asia, yet it is surprising that it has taken so long for a comprehensive reference source on this religion to appear. Macmillan's work covers not only the familiar topics found in many existing titles on Buddhism but delves deeper. Some 250 experts have crafted scholarly yet accessible articles on nearly 500 topics ranging from rituals and practices to art and Western influence."--"Reference that rocks," American Libraries, May 2005.
v. 1. A-L -- v. 2. M-Z, appendix, index.
Includes bibliographical references and index.
Keywords: Patrimoines (Editions du Cerf).; Buddhism -- Encyclopedias